Knowledge and attitude towards willingness to perform cardiopulmonary resuscitation among undergraduate nursing students in School of Health Sciences, Universiti Sains Malaysia - Ping, Wong Siew (Universiti Sains Malaysia, 2013)
Cardiopulmonary resuscitation (CPR) is a critical component of basic life support (BLS) and the established first-line of response to a cardiac arrest in the interim before defibrillation and advance life support (ALS) are performed. Evidence suggests that CPR knowledge and skills are poorly retained across health care professionals, including nursing students. This is a cross-sectional, descriptive study. This study was designed to provide an understanding of nursing students' knowledge, attitude and willingness to CPR. A purposive sample of 96 undergraduate nursing students from the Nursing Programme, School of Health Sciences, Universiti Sains Malaysia participated in this study during December 2012 to February 2013. Questionnaires were used to gather the data. Descriptive statistics, independent t-test, one way ANOVA, and Pearson correlation coefficients with SPSS version 20.0 were used for data analysis. The results show that the mean score for knowledge regarding CPR was 10.84 of a total possible score of 20 and for attitude, 30.41 of a total possible score of 50. There was no correlation between age with CPR knowledge and attitude towards willingness to perform CPR. There was no correlation between gender and attitude towards willingness to perform CPR. However, there was positive correlation between gender and knowledge regarding CPR. In conclusion, in order to develop positive attitudes in nursing students towards the performance of CPR, we need to strengthen education related to CPR and create effective education programs which are focused particularly on practical training for the students.